Criteria of Pedagogical Practices in Times of Pandemic: A Systematic Review - Ayala-Mendoza, Asdrúbal (2023)
The COVID-19 pandemic has posed significant challenges to the field of education, requiring pedagogical practices to swiftly evolve from technological and socioformative perspectives, as well as the incorporation of other pedagogical practices that dominated the teacher-student interaction during the pandemic to ensure the continuity of ongoing academic cycles. The objective is to characterize the criteria that can be derived from pedagogical practices during the 2020–2022 pandemic period. A qualitative and quantitative evaluation of authors’ contributions was conducted through a systematic review based on the PRISMA 2020 guidelines using SCOPUS and Web of Science (WoS) databases. Boolean equations based on keywords were employed for publication filtering. Cohen's Kappa index was calculated to assess review concordance. The analysis reveals that pedagogical practices influence the deficient technological inclusion of teachers’ skills. Socioformation shows a shift from traditional characteristics in teaching processes. Additionally, there is openness to the inclusion of new pedagogical practices associated with digital education and virtual environments. Technology and methodology integrate co-evaluation, feedback, and interactive methodologies as alternatives for enhancing acquired and inherent technological skills in virtual classrooms using technological platforms.